Can forest conservation and logging activities be reconciled for sustainable future? A case of Deramakot Forest Reserve in Borneo / Silverina Anabelle Kibat, Anderson Ngelambong and Vickson E Tabak - Kibat, Silverina Anabelle; Ngelambong, Anderson; Tabak, Vickson E (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Sabah has a long history in the timber industry. While no doubt that logging is a significant source for local economies, it can also contribute to deforestation and forest degradation. Due to the critical importance of timber to human society has led to active logging activities that fail to consider the long-term impact on the forest ecosystems and all who depend on them. The forest in Sabah was fast depleting and the only option was to manage it sustainably or risk losing this economic resource. Because of this, Deramakot Forest Reserve was chosen for sustainable forest management by the Forest Department in Sabah with technical help from the German Agency for Technical Cooperation (GTZ). This paper identifies the success of Deramakot Forest Reserve in becoming the first and longest tropical rainforest in the world to receive the Forest Stewardship Council (FSC) gold standard in forest management, how their Forest Management Plan (FMP) has to produce ecologically sustainable timber and taking into consideration the needs of indigenous people who live within the area and today is one of the most diverse wildlife sanctuaries in world.